O sistema brasileiro de unicidade sindical e compulsoriedade de representação - Pereira Neto, João Batista (2016)
The Brazilian labor union system has as its two main characteristics the single-laborunion rule and the compulsory representation, both of which contribute to a not very effective environment for collective bargaining. This essay proposes a reflection about that reality and, for this purpose, presents a detailed examination of the Brazilian labor union system, including the study of the history of the workers associations in unions and the legislative development in Brazil on this subject until the current structure was established. From this analysis, a few particularities of the union structure and of the environment in which the collective bargaining is developed will be presented, what will allow understanding the issues and interests involved and the reason of the resilience to reform the current labor union system. Finally, this essay debates the necessity of adopting the unrestricted union freedom in Brazil, as a method to solve the crisis of union representativeness and to recognize the fundamental right of liberty